Climate Services to Support Disaster Risk Reduction and Climate Change Adaptation in Urban Areas: The CLARITY Project and the Napoli Case Study - Zuccaro, Giulio; Leone, Mattia Federico (Frontiers in Environmental Science, 2021)
Climate Services are emerging worldwide as an essential tool to bridge the advancement in climate science and meteo/earth observations with a variety of operational fields in the domains of Disaster Risk Reduction (DRR) and Climate Change Adaptation (CCA). It is multidisciplinary study area with promising applications in the field of urban microclimate simulations, supporting climate-resilient redevelopment actions at both city and neighbourhood level. The CLARITY CSIS (Climate Services Information System, available at https://csis.myclimateservice.eu/), developed within the H2020 CLARITY project, is an innovative hazard/impact modelling tool that takes into account short- to long-term climate change scenarios and urban microclimate variability. Disaster risks associated to climate-change, such as heat waves and floods, are concentrated in limited periods of the year and therefore not adequately represented by annually averaged values. To this aim, new datasets have been extracted from Regional Climate Models to estimate the frequency of extreme temperatures and precipitation events until 2100, and a novel modelling methodology has been developed to capture the effect on the urban microclimate due to specific built environment features. The wide amount of data generated by satellite earth observations and made available at pan-European level through the Copernicus datasets (e.g. Urban Atlas, European Settlement Map, etc.), hae been processed through specific algorithms and GIS spatial analysis tools to extract detailed information related to key parameters linked to urban morphology and surface types. In addition to the “screening service” available at pan-European level through the CLARITY CSIS, an “Expert Service” workflow allows to increase the resolution of hazard and impact simulations at 250m, by exploiting detailed land use datasets provided by local end-users, and to assess the DRR/CCA potential of city-wide adaptation plans, as well as of specific district redevelopment projects. This paper will present the features of CLARITY CSIS and the results of Expert Services implemented for the City of Naples, focusing on the methods adopted to implement hazard/impact assessments and how information from climate services is tailored to support the integration of different DRR/CCA strategies within urban plans and projects.